PENGARUH BIMBINGAN DAN KONSELING PADA ANAK SEKOLAH DASAR TERHADAP KEHIDUPANNYA SEHARI-HARI - MUSTAFA MUSTAFA (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Abstract. After an influential family role in the life of a child, the role of the school environment has a second position in the process of growth and development in daily life, because it can be said for 24 hours, about a few percent of the child's time spent at school. The role of this education aims to educate the nation's life and develop Indonesian people as a whole, namely people who have faith, are virtuous, have knowledge and skills, physical and spiritual health, a steady and independent personality, and a high sense of responsibility in society. To achieve all of that, students or students must be able to develop optimally with appropriate abilities, this is where the role of education is not only to help develop intellectual abilities, but also the ability to overcome problems in themselves in interacting with their environment. Schools not only serve to provide knowledge in teaching and learning activities, but schools also function in developing the character and personality of children. Therefore, teachers must know more than just the problem of how to teach effectively. But he must also be able to assist students in developing all aspects of their personality and environment, as long as it is professionally possible. In an effort to help students, teachers need to know the foundation, concepts, procedures, and practice of counseling guidance.